2006
DOI: 10.1530/eje.1.02112
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 12-month treatment with the GH receptor antagonist pegvisomant in patients with acromegaly resistant to long-term, high-dose somatostatin analog treatment: effect on IGF-I levels, tumor mass, hypertension and glucose tolerance

Abstract: Objective: We aimed to investigate the efficacy of pegvisomant in patients with acromegaly resistant to long-term (^24-month), high-dose treatment with octreotide-LAR (40 mg/month) or lanreotide (120 mg/month). Design:This was an open, prospective study. Subjects and Methods: We studied 16 patients with acromegaly (nine women; aged 28 -61 years). The main outcome measures were IGF-I levels, blood pressure, glucose tolerance and safety (liver function and tumor size). Pegvisomant was given at doses of 10-40 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
106
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(119 citation statements)
references
References 38 publications
9
106
0
4
Order By: Relevance
“…Pegvisomant is highly effective in normalizing IGF-I levels, even in patients resistant to other treatments (30), and this was confirmed in our series with a high percentage (85%) of disease control. Our results are closer to the data reported in the initial clinical trials with pegvisomant monotherapy and those from series of other tertiary centers than to the data reported in the last update of the Acrostudy (20)(21)(22)31,32).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Pegvisomant is highly effective in normalizing IGF-I levels, even in patients resistant to other treatments (30), and this was confirmed in our series with a high percentage (85%) of disease control. Our results are closer to the data reported in the initial clinical trials with pegvisomant monotherapy and those from series of other tertiary centers than to the data reported in the last update of the Acrostudy (20)(21)(22)31,32).…”
Section: Discussionsupporting
confidence: 83%
“…Acromegaly is associated with enhanced mortality and a high morbidity when normalization of GH and IGF-I levels is not achieved (2). Although surgery and tumor-directed drugs (SA and DA) permit disease control in the majority of patients, there are some cases that require additional treatments (4,30). In our series, the majority of patients (78%) were submitted to surgery, and all but one patient was treated with first-generation SA, with association with cabergoline tried in 78%.…”
Section: Discussionmentioning
confidence: 99%
“…All progressions were relatively minor size increases that could not be recognized clinically. Other reports of tumor size increase (5,13,15,(18)(19)(20) did not pay tribute to potential tumor size increase before pegvisomant therapy and also did not evaluate for potential somatostatin induced tumor shrinkage and subsequent rebound, although in an individual patient such a course is described (13). In this cohort and in the medical literature, except for one patient, whose tumor progression occurred during combination therapy with pegvisomant and somatostatin analogs (19), all hitherto reported tumor size increases were observed during monotherapy with pegvisomant (20).…”
Section: Discussionmentioning
confidence: 78%
“…The pivotal studies had demonstrated its safety and efficacy (4,5). However, while in the clinical studies up to 97% of patients treated with this drug achieved normal IGF1 levels (4,5,13), the GPOS found much lower normalization rates (7,8) reaching a maximum of 71.3% at 24 months. It reflects the reality of patient care in difficultto-treat acromegaly.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to SSA, PEG decreases fasting plasma glucose (Urbani et al 2013) and improves glucose tolerance (Colao et al 2006) and insulin sensitivity (Schreiber et al 2007). Switching from SSA to PEG significantly improves diabetes control in diabetic ACM cases .…”
Section: Medical Treatmentmentioning
confidence: 99%